Dungeons & dragons and philosophy : read and gain advantage on all wisdom checks - Robichaud, Christopher (Chichester, West Sussex ; Malden : Wiley-Blackwell, 2014)
Do demons and devils have free will? Does justice exist in Menzoberranzan? What's the morality involved with player characters casting necromancy and summoning spells? Dungeons & Dragons and Philosophy probes the rich terrain of philosophically compelling concepts and ideas that underlie Dungeons & Dragons, the legendary fantasy role-playing game that grew into a world-wide cultural phenomenon. A series of accessible essays reveals what the imaginary worlds of D & D can teach us about ethics, morality, metaphysics and more. Illustrates a wide variety of philosophical concepts and ideas that ar.
Includes index.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Dungeons and Dragons (Game); Philosophy; GAMES -- Board; Dungeons and Dragons (Game); Philosophy; Electronic books